2023
DOI: 10.1101/2023.01.03.522478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photomanipulation of minimal synthetic cells: area increase, softening and interleaflet coupling of membrane models doped with azobenzene-lipid photoswitches

Abstract: Light can effectively interrogate biological systems providing control over complex cellular processes. Particularly advantageous features of photo-induced processes are reversibility, physiological compatibility, and spatiotemporal precision. Understanding the underlying biophysics of light-triggered changes in bio-systems is crucial for cell viability and optimizing clinical applications of photo-induced processes in biotechnology, optogenetics and photopharmacology. Employing membranes doped with the photol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 127 publications
4
9
0
Order By: Relevance
“…We did, however, find a modest (∼1%) irreversible volume expansion with UV irradiation with pure azo-PC, which might indicate that a small amount of glucose permeated the membrane. Overall, our results agree with a recent study of azo-PC that found no exchange of sugar across the membrane . By contrast, another recent study reported a higher permeability of a fluorophore when azo-PC was in cis compared to trans state .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We did, however, find a modest (∼1%) irreversible volume expansion with UV irradiation with pure azo-PC, which might indicate that a small amount of glucose permeated the membrane. Overall, our results agree with a recent study of azo-PC that found no exchange of sugar across the membrane . By contrast, another recent study reported a higher permeability of a fluorophore when azo-PC was in cis compared to trans state .…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our results agree with a recent study of azo-PC that found no exchange of sugar across the membrane. 20 By contrast, another recent study reported a higher permeability of a fluorophore when azo-PC was in cis compared to trans state. 11 (The UV intensity at the sample was not reported, but the timescales for the response appear comparable to ours, suggesting that the light intensity was similar.)…”
Section: ■ Materials and Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Synthetic lipids can further be functionalized with a variety of synthetic polymers or interacting groups, e.g., poly(ethylene glycol) (PEG) linkers, fluorescent labels, nickel chelating groups, or azobenzene moieties. This functionalization can provide additional properties to the membrane, such as reducing nonspecific interactions, [42] generating photoswitchable lipids, [43] selective anchoring of molecules or proteins to the inner or outer leaflet, and more. In biological membranes, the bilayer is compositionally asymmetric, with the inner leaflet being different in lipid and protein composition from the outer leaflet.…”
Section: Guvs As the Container For Artificial Cells-what Are The Requ...mentioning
confidence: 99%
“…It would be more interesting to see what the impact of the azobenzene lipid is in more complex lipid mixtures resembling the situation found in natural membranes. Following this idea, Aleksanyan et al [26] recently investigated the impact of the isomerization of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) monolayers and GUVs containing different 18 : 0-azoPC concentrations ranging from 5-50 mol %. They showed that the isomerization-induced reversible membrane deformation, as well as membrane thinning, and area increase were a function of the photo-lipid concentration.…”
Section: Control Of Membrane Physico-chemical Properties By Photo-lipidsmentioning
confidence: 99%